Flood in the desert [videorecording (DVD)] - Rapley, Rob; Braugher, Andre; Montoya, María E., 1964-; Bsumek, Erika Marie; Deverell, William, 1962-; Halpern, Nathan, 1978- (PBS, 2022)
Presents the story the Los Angeles Aqueduct, which brought water across the Mojave Desert to Los Angeles in 1913, and the 1928 St. Francis Dam collapse, the second deadliest disaster in California history, killing more than 400 people.